Evidence for valence fluctuation in the CeSn3 compound - Sereni, J.G.; Sereni, Julián (IOP Publishing, 1980)
Fil: Sereni, J. G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina